PENGARUH GREEN ACCOUNTING, INTELLECTUAL CAPITAL, TAX PLANNING, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Putri, Ayudiyah; Yantiana, Nella (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
Purpose: This study aims to determine the effect of green accounting, intellectual capital, tax planning, and leverage on company value, Methods: The research used a quantitative approach obtained from secondary data, namely financial reports of basic industry companies listed on the Indonesia Stock Exchange, with purposive sampling technique., Analysis data: The data were analyzed using multiple linear regression with SPSS version 26, Result and discussions: The results of this study indicate that green accounting, tax planning, and leverage affect company value, while intellectual capital does not affect company value., Conclusion: Based on the findings of this study, companies can consider effective measures in implementing green accounting and tax planning within their companies, as well as maintaining a stable debt level in order to achieve the expected company value. Further research can explore the influence of intellectual capital on other sectors in order to gain a more comprehensive understanding.